HUBUNGAN POWER OTOT TUNGKAI DENGAN KECEPATAN TENDANGANMAWASHI GERIPADA ATLET PUTRA CLUB TAKO HANGTUAH (DOJO KULIM) PEKANBARU - Darma Julianti Sapona; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of this research is that during the kumite training there are still many karate who are not quick enough to do the mawashi geri kick. The goal is to find out how much the correlation between leg muscle power and the speed of kicking mawashi is for the male athlete tako Hangtuah (Kulim Dojo) Pekanbaru. This research technique uses total sampling with a sample size of 15 athletes of the male dojo Kulim Pekanbaru. This research uses correlation techniques. Then, the test data used the normality test, the moment correlation product test, a significant test α = 0.05. Normality test variable X, L0max (0.1651) <Ltabel (0.220), and variable normality test Y, L0max (0.1359) <Ltabel (0.220) in other words the confidence level of 95% normal data and research conclusions indicate: a significant correlation between the correlation of arm and shoulder muscle explosive power to the results of the shot, with a correlation r = 0.7127 where r count> rtabelor 0.7127> 0.514. And correlation are categorized as strong. Thus, Ha is accepted.Keywords: Correlation, Leg Muscle Power, Kick Speed.